TRADISI PEMBACAAN ZIKIR GHOFILIN DENGAN TATA CARA KHUSUS DI PONDOK PESANTREN NURUSSALAM TENGGARONG SEBERANG - Nayliya Syafi'i, Ridha; Mursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores the tradition of Zikrul Ghofilin practiced with a specific procedural system at Pondok Pesantren Nurussalam, Tenggarong Seberang. This tradition is considered a collective effort to increase spiritual awareness, strengthen the inner state, and remind individuals who are spiritually heedless (al-ghofilin) to return to the remembrance of Allah. The purpose of this research is to identify, describe, and analyze the detailed procedures of the Zikrul Ghofilin practice carried out in the pesantren community. This study uses a qualitative field research approach, with primary data obtained through interviews with pesantren residents and participants of the ritual, as well as direct observation of its implementation. Secondary data were collected from relevant documents, books, and journal articles supporting the discussion. Data analysis was conducted using a descriptive qualitative method to interpret the ritual stages and their underlying meaning. The findings show that the practice of Zikrul Ghofilin at Pondok Pesantren Nurussalam is performed in two forms: (1) collective zikr conducted aloud (jahr), consisting of a sequence of activities including sunnah prayers, classical book recitation, tawassul, and the structured recitation of Zikrul Ghofilin; and (2) individual zikr performed silently (sirr) with specific hand placements on several spiritual points (lathāif) as a symbolic effort to purify the heart and strengthen spiritual consciousness. This study highlights that the tradition not only functions as religious practice but also as a form of living Qur’an manifestation within the local pesantren community.